Mengungkap kekerasan seksual di dunia pendidikan Indonesia: Suara yang terpendam, tantangan, dan jalan menuju perlindungan - Muchammad, Haidar (Maliki Interdisciplinary Journal, 2024)
The issue of sexual violence in Indonesian schools has grown to be complex and concerning. We will address the phenomenon in this paper by describing the unsung voices of victims, the difficulties in addressing sexual violence in the classroom, and practical steps taken in the direction of better protection. This paper aims to raise public awareness of the effects of sexual violence in education and to motivate proactive steps toward creating a supportive and safe learning environment..